THE IMPACT OF TRAUMATIC BRAIN INJURY ON PATIENT-REPORTED PHYSICAL AND MENTAL HEALTH. Issue 11 (14th October 2015) - Gorgoraptis, Nikos; Zaw-Linn, Joanna; Feeney, Claire; Jimenez, Carmen Tenorio; Niemi, Mari; Malik, Aysa; Ham, Timothy; Baxter, David; Goldstone, Anthony; Sharp, David
Abstract : Traumatic Brain Injury (TBI) is a major cause of disability, with staggering social consequences, but little is known on what determines the impact of TBI from the patient's perspective. In an audit of 240 patients (172 males, median age: 42 years, range: 20–89 years) who attended our multidisciplinary TBI clinic, we examined the impact of cognitive function, depression, sleep, history of substance abuse, age, injury severity (172 moderate-severe, 68 possible-mild TBI) and time since injury (median: 4 months, range: 20 days–28 years) on two patient-reported measures of quality of life: SF–36 Health Survey and Nottingham Health Profile (NHP). Worse outcomes in NHP and both Mental and Physical sub-scores of SF–36 were associated with poorer cognitive performance, as measured by ACE–R. Depression, examined using BDI–II, showed a strong negative correlation with both quality of life measures. Sleep-related symptoms were also strongly associated with worse patient-reported outcomes. Patients reported poorer outcomes in both SF-36 and NHP when examined at a later time since their injury, and this effect could not be attributed to older age. Impairments in cognition, mood and sleep following TBI may have a significant impact on patients' perception of their physical and mental well-being.